2015
DOI: 10.1103/physrevlett.114.075501
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Bidentate Thiolate Ligands on Gold Surfaces

Abstract: The effect of the chain length separating sulfur atoms in bidentate thiols attached to defective gold surfaces on the rupture of the respective molecule-gold junctions has been studied computationally. Thermal desorption always yields cyclic disulfides. In contrast, mechanochemical desorption leads to cyclic gold complexes, where metal atoms are extracted from the surface and kept in tweezer-like arrangements by the sulfur atoms. This phenomenon is rationalized in terms of directional mechanical manipulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Moreover, the mechanical stability of catechol–Fe 3+ bonds is also similar to other coordination bonds reported in literature, but are significantly lower than that of covalent bonds. The mechanical stability of a bond is not just determined by its bond strength. Instead, it is determined by the free energy barrier as well as the position of the transition state.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the mechanical stability of catechol–Fe 3+ bonds is also similar to other coordination bonds reported in literature, but are significantly lower than that of covalent bonds. The mechanical stability of a bond is not just determined by its bond strength. Instead, it is determined by the free energy barrier as well as the position of the transition state.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, the general physical concepts that describe the way in which an external force accelerates the rate of transition over an energy barrier were first presented at the beginning of the last century by Prandtl and also used by Eyring to model fluid viscosity as well as other mechanically induced processes . They have also been used to describe nanoscale friction measured in the AFM by the so-called Prandtl-Tomlinson model. , Molecular simulations have been carried out for alkyl thiolate species on coinage metal surfaces ,, to probe the molecular mechanisms occurring under normal and lateral stresses. Such theoretical studies have suggested that shear of alkyl thiolate-covered silver and gold can occur within the metal substrate and can result in the evolution of metal-containing species, not observed for a pin sliding over copper.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of bidentate organic linkers can lead to the formation of discrete structures (d = 0) such as molecular complexes or salts. [110][111][112] However, there are very few reports focusing on studies of the electronic properties of these structures. [113] One well-known example is based on the preparation of salts of H 2 AzoBPDC (H 2 AzoBPDC = (E)-4,4′-(diazene-1,2-diyl) dibenzoic acid; c = 2; Figure 14) that were studied for modulating ionic conductivity through azobenzene photoisomerization.…”
Section: Functionalization Of 0d Materials With Photochromic Molecule...mentioning
confidence: 99%